Bleomycin A5 sclerotherapy for cervicofacial lymphatic malformations - Yang, Yaowu; Sun, Moyi; Ma, Qin; Cheng, Xiaobing; Ao, Jianhua; Tian, Lei; Wang, Lei; Lei, Delin (Journal of vascular surgery, 2011)
The purpose of this study was to document the results of bleomycin A5 sclerotherapy for cervicofacial lymphatic malformations (LMs), and the clinical data of 65 patients between October 2004 and October 2007 were reviewed. Of the 65 patients in the study, 60 patients were given intralesional injection of bleomycin A5. Five patients underwent partial resection, and then an injection of bleomycin A5 for the remaining lesion. The outcomes were assessed by physical examination and Doppler ultrasonography scan. The follow-up time was from 6 months to 3 years after the last injection (mean, 16 months). Among the 65 patients, 41 were men and 24 were women (1.7:1 male:female ratio), the age range was 3 months to 45 years (mean, 12 years). Thirty-two lesions (49%) were macrocystic, 30 (46%) were microcystic, and 3 (5%) were combined. Each patient received 1 to 10 injections (mean, 3.0 injections) for the whole course of treatment, and the total dose of bleomycin A5 was from 8 to 80 milligrams (mean, 24.0 mg). Twenty-six of 32 macrocystic lesions (81%) showed greater than 90% reduction, whereas another 6 (19%) exhibited 50% to 90% reduction. Nineteen of 30 microcystic lesions (63%) showed greater than 90% reduction; 10 (33%) had 50% to 90% reduction; and 1 (4%) had less than 50% size reduction. Of the 3 combined lesions, 2 (67%) had greater than 90% shrinkage, and 1 (3%) had less than 50% reduction. The complications included ulceration of oral mucosa, minor soft tissue atrophy, mild fever, and hematoma. There was no recurrence throughout the follow-up period. These data suggest bleomycin A5 is a safe and effective intralesional agent for the treatment of macrocystic LMs, superficial oral mucosa LM, and localized deep microcystic lesions. For extensive macrocystic LMs involving contiguous anatomic areas and diffuse microcystic lesions involving deep tissues, bleomycin A5 injection combined with resection is necessary.